Pengembangan Sistem Marketplace Tempat Aktivitas Edukatif Anak Berbasis Mobile iOS - Faiqotul Himmah; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
There has arisen awareness of some people in meeting educational needs that help their children grow up at an early age. It's just, still often encountered difficulties when parents want to find a place for educational activities, especially those that are friendly to children. Based on that, a Parentstory system has been created to find and locate children's educational activities in Jabodetabek with website-based. However, in a condition where people are increasingly aware of the use of gadgets, providing a website-based system is not yet practical. Therefore, a system is needed that can also be developed in the form of a mobile application to increase system service penetration, especially to people who use iOS-based gadgets. The problem faced in providing the intended application is how needs analysis, design, implementation, and testing must be carried out so that the application is easy to use in accordance with the needs of the community. Based on the above problems, this research is carried out to develop iOS-based mobile applications as a means to find, discover and place reservations for children's educational activities, especially in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas. This study began with a needs analysis that found 25 functional system requirements. Next, a design with Model View Controller (MVC) and a MySQL database are implemented which is implemented using Swift language. The testing phase is done by white and black box test methods. White box testing is done by unit testing. While black box testing uses validation testing which produces a 100% valid value for all test cases where the application made is in accordance with the results of previous analysis and design, and usability testing which produces an 80.4 value with an acceptable category.